Profile Of The Use Of The Drug In Patients Acute Respiratory Tract Infection In Child Patients Aged 5-10 Years: Profil Penggunaan Obat Pada Pasien Infeksi Saluran Nafas Akut (ISPA) Pada Pasien Anak Usia 5-10 Tahun - irma novrianti, Irma (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Acute respiratory tract infection is a disease that is often experienced by toddlers and children caused by bacterial, viral infections, without or accompanied by lung parenchyma. The purpose of this study was to determine the therapy used in ARI patients at the Puskesmas